2021
DOI: 10.34172/aim.2021.62
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Characteristics of Hospitalized COVID-19 Patients in Hormozgan, Iran: A Retrospective, Multicenter Study

Abstract: Background: To better manage the COVID-19 pandemic, it is necessary to carefully study information about patients with COVID-19. Objective: To report clinical and epidemiological characteristics of COVID-19 patients in southern Iran. Methods: This cross-sectional retrospective study was conducted based on data extracted from the COVID-19 registry of Hormozgan. Data from patients with confirmed COVID-19 based on CT-scan results or real-time reverse transcriptase-polymerase chain reaction (RT-PCR) results until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…After screening by abstract and title, 571 articles were selected for full-text assessment. In total, 157 studies evaluating 948,309 patients were included in the meta-analysis (9–159). The characteristics of all the included studies are shown in Table S1 (http://links.lww.com/CCX/B152).…”
Section: Resultsmentioning
confidence: 99%
“…After screening by abstract and title, 571 articles were selected for full-text assessment. In total, 157 studies evaluating 948,309 patients were included in the meta-analysis (9–159). The characteristics of all the included studies are shown in Table S1 (http://links.lww.com/CCX/B152).…”
Section: Resultsmentioning
confidence: 99%
“… 24 In a cross-sectional retrospective study that was conducted in Iran, 64.5% mortality rate (147 of 228) in ICU wards was reported. 17 In a larger sample of patients with COVID-19 admitted to ICUs in public hospitals of Abu Dhabi, 12.7% of 1542 ICU admitted patients died. 16 The reasons for the observed variability in ICU admission and ICU mortality between the studies are multifactorial and may reflect the variations in the number of patients included in the analysis, disease severity and clinical characteristics of patients such as those who received invasive mechanical ventilation, critical care capacity and setting, or treatment procedures.…”
Section: Discussionmentioning
confidence: 99%
“…These findings emphasized what was reported in countries with close sociodemographic characteristics. 15 , 16 , 17 , 18 For instance, in addition to age, diabetes was associated with admission to the ICU in patients with COVID-19 in Kuwait (OR 1.78 [95% confidence interval 1.17-2.70]). 15 Several studies examined the factors associated with ICU admission and poor outcomes among patients hospitalized with COVID-19 overall the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation